PEER TEACHING-BASED LEARNING ASSISTED BY MANIPULATIVE MEDIA IN IMPROVING STUDENTS' UNDERSTANDING AND SKILLS IN ADVANCED MATHEMATICS COURSES - Syarifuddin, Syarifuddin (MATEMATIKA DAN PEMBELAJARAN, 2025)
This study aimed to analyze peer teaching-based learning assisted by manipulative media in improving students' understanding and skills in advanced mathematics courses. The study employed a descriptive quantitative approach along with a qualitative approach, involving 32 students from the PGMI program, semester 3, at the University of Muhammadiyah Bima. The research instrument were the tests to measure understanding and media development skill. Then the second instrument were the questionnaires to measure students' perceptions of the learning process, media development, and understanding. Data were analyzed using descriptive qualitative for the description of test answers, and descriptive statistics for the questionnaire results. The results showed that students' perception of the peer teaching process assisted by manipulative media was rated as very good (75%), the development of learning media was rated as very good (78.13%), and students' understanding of advanced mathematics material was rated as very good (68.75%). Students' learning outcomes met the graduation criteria with 100% of students achieving the required passing grade, supported by excellent peer teaching skills. The findings concluded that the application of peer teaching assisted by manipulative media can enhance students' motivation and positive perceptions of the mathematics learning process, increase creativity in developing relevant and interactive concrete media, and optimize students' conceptual understanding and analytical skills.